In vitro investigation of cytotoxic and antioxidative activities of selected Malaysian plants - Nordin, Muhammad Luqman (2017)
Mammary cancer cases continue to increase yearly due increasing of the population. The incident rate of mammary cancer amongst humans and animals are high. The drug resistance and long-term side effects issues eventually necessitate scientist to discover and explore new source of treatment such as from herbs that perhaps can encounter the issues.This study was conducted to screen the cytotoxic effect of hydromethanolic crude extract from leaves of Ardisia crispa (HEAC), Tetracera indica (HETI), Aquilaria Malaccensis Lam (HEAM) and Syzygium Polyanthum (Wight) Walp (HESP), towards animal and human mammary cancer cell lines. The cytotoxic effect of hydromethanolic leaves extracts was determined with MTT assay against various mammary cancer cell lines (4T1, MCF-7, CMT-Stylo, MDA-MB-231). Among mammary cancer cell lines tested, 4T1 and MCF-7 showed significant reduction of cell viability with IC50 value of 42.26 ± 1.82 μg/mL and 52.41 ± 3.49 μg/mL, respectively after 72 hours of treatment. Thus, HEAC was further evaluated for its anti-mammary cancer and antioxidant properties. HEAC was partitioned using ethyl acetate and aqueous to obtain ethyl acetate (EAEAC) and aqueous (AQEAC) fractions of A. crispa, respectively. The EAEAC and AQEAC were screened for cytotoxic effects using MTT assay against 4T1, MCF-7, CMT-Stylo and MDA-MB-231 and the IC50 values results were compared with HEAC. Selectivity index (SI) of HEAC, EAEAC and AQEAC were also estimated by comparing IC50 value of extracts of 4T1 against CC50 value of extracts against NIH3T3 (mouse fibroblast cell line). HEAC had the highest SI value indicating that HEAC can be classified as a potential agent for anti-mammary cancer, being toxic only to the cancer cells but not to the normal cells. Antioxidant capacity of the HEAC, EAEAC and AQEAC were assessed using DPPH (1,1-diphenyl-1-picrylhyrazyl) and ABTS (2, 2’-azinobis (3-ethylbenzothiazoline-6-sulphonic acid) free radical scavenging assays. Phytochemical screening, total phenolic content (TPC) and total flavonoid content (TFC) were also determined and analysed. Generally, A. crispa has good antioxidant capacity contributed with the presence of high phenolic and flavonoid compounds. The mechanism of cell death was assessed using Acridine Orange/Propidium iodide (AO/PI) and Annexin V-FITC/PI on 4T1 cells. The morphology results of AO/PI showed that majority of untreated cells emitted green fluorescence colour whereas in treated cells, there were mixtures of colour including orange which indicated apoptosis and red fluorescence colour indicated cell death. The confirmation of cell death event which was mainly apoptosis was further proven using Annexin V-FITC/PI staining through flow cytometer. The cells were labelled and differentiated into four quadrate based on the stage of the cells; viable, early apoptosis, late apoptosis and necrosis. Apoptosis occurred as early as 6 hours. The percentages (%) of early and late apoptosis were 8.30 ± 1.11 and 0.70 ± 0.42, respectively. There was no apoptosis event (0%) in untreated cells (control). In conclusion, HEAC showed potential anti-mammary cancer effect and antioxidative activity. The extract able to inhibit cancer cell proliferation through apoptosis, suggesting cancer cell cycle arrest at sub G0/G1 phase.